Mapping of quantitative trait loci controlling tick [Riphicephalus (Boophilus) microplus] resistance on bovine chromosomes 5, 7 and 14 - Gasparin, G.; Miyata, M.; Coutinho, L. L.; Martinez, M. L.; Teodoro, R. L.; Furlong, J.; Machado, M. A.; Silva, M. V. G. B.; Sonstegard, T. S.; Regitano, L. C. A. (Blackwell Publishing, 2007)
Differences in domestication and selection processes have contributed to considerable phenotypic and genotypic differences between Bos taurus and Bos indicus cattle breeds. of particular interest in tropical and subtropical production environments are those genetic differences between subspecies that underlie the phenotypic extremes in tolerance and susceptibility to parasite infection. In general, B. taurus cattle are more susceptible to ectoparasites than B. indicus cattle in tropical environments, and much of this difference is under genetic control. To identify genomic regions involved in tick resistance, we developed a B. taurus x B. indicus F-2 experimental population to map quantitative trait loci (QTL) for resistance to the Riphicephalus (Boophilus) microplus tick. About 300 individuals were measured for parasite load in two seasons (rainy and dry) and genotyped for 23 microsatellite markers covering chromosomes 5, 7 and 14. We mapped a suggestive chromosome-wide QTL for tick load in the rainy season (P < 0.05) on chromosome 5. For the dry season, suggestive (P < 0.10) chromosome-wide QTL were mapped on chromosomes 7 and 14. The additive effect of the QTL on chromosome 14 corresponds to 3.18% of the total observed phenotypic variance. Our QTL-mapping study has identified different genomic regions controlling tick resistance; these QTL were dependent upon the season in which the ticks were counted, suggesting that the QTL in question may depend on environmental factors.
Keywords: cattle; ectoparasites; microsatellite marker; quantitative trait loci; resistance